The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1101/2020.05.08.20095588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mathematical model of COVID-19 spread in Turkey and South Africa: Theory, methods and applications

Abstract: A comprehensive study about the spread of COVID-19 cases in Turkey and South Africa has been presented in this paper . An exhaustive statistical analysis encompassing arithmetic, geometric, harmonic means, standard deviation, skewness, variance, Pearson and Spearman correlation was derived from the data collected from Turkey and South Africa within the period of 11 . It was observed that in the case of Turkey, a negative Spearman correlation for the number of infected class and a positive Spearman correlation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 13 publications
0
61
0
Order By: Relevance
“…It is very necessary to ensure that, the proposed optimal solution exists. For this reason, we employ Filippove-Cesari theorem as used in [37] . In this case, we show that, the existence of the optimal control solution is guaranteed if the following conditions are satisfied; The admissible control set is compact and bounded.…”
Section: Optimal Control On the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It is very necessary to ensure that, the proposed optimal solution exists. For this reason, we employ Filippove-Cesari theorem as used in [37] . In this case, we show that, the existence of the optimal control solution is guaranteed if the following conditions are satisfied; The admissible control set is compact and bounded.…”
Section: Optimal Control On the Modelmentioning
confidence: 99%
“… A linear function in the state and control variables bound the state systems of differential equations. The convexity of the integrand of cost functional with respect to u on the set A [37] . …”
Section: Optimal Control On the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of [8] has characterized the epidemic of COVID-19 in Heilongjiang province. For more works, interested readers are referred to [9] , [10] , [11] , [12] , [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Some parameters were used to calibrate the parameters of the SIRD model on the reported COVID-19 cases in Hubei region, China, the selected model was used to forecast the evolution of the outbreak at the epicenter for three weeks ahead [16]. A comprehensive comparison was carried out on COVID-19 cases using some mathematical model between Turkey and South Africa [17]. It is against this background that this study attempts to model the daily cumulative active, critical and confirmed COVID-19 cases as it influences the number of reported deaths in Nigeria between 28 th of February to 6 th of July 2020, using count regression models like; Poisson Regression (PR), Negative Binomial Regression (NBR) and Generalized Poisson Regression (GPR) models.…”
Section: Introductionmentioning
confidence: 99%